Simple model for time-dependent bond transfer in pretensioned concrete using draw-in data. (1st April 2018) - Floyd, Royce W.; Pei, Jin-Song; Wright, Joseph P.
Highlights: A model for time dependent prestress loss and bond-transfer is presented. Strand draw-in measurements are used for transfer length. A one-dimensional linear viscoelastic standard solid model is used for creep. Verification with experimental data demonstrates the potential of the model. Abstract: Time evolution of prestress loss and bond transfer length holds vital information concerning long-term performance of pretensioned prestressed concrete. In this paper, it is proposed to utilize long-term measurements of strand draw-in to extract this time-varying information, which could be more effectively obtained than concrete or strand surface strain measurements. Theoretical investigations combined with numerical studies of experimental data are carried out for this purpose. This study builds on Guyon's boundary value problem (BVP) model which quantifies draw-in for instantaneous elastic response. A one-dimensional linear viscoelastic standard solid model is employed to model the creep of concrete, which is a simple but effective model of the time-dependent response of concrete. Guyon's BVP model is generalized to include time dependence and then combined with an existing initial value problem (IVP) model for post-tensioned concrete leading to a new mixed model for time-dependent prestress loss and bond transfer in pretensioned concrete. Analysis is undertaken in this study to (i) quantify long-term prestress loss and bond-transfer behaviors by applying the proposed model and directly utilizing measured draw-in time history data, (ii) validate the proposed quantitative analysis by using scaled pretensioned concrete beams with different types of aggregates and strengths of concrete - among other factors, and (iii) offer discussion of future work. For example, introducing concrete drying shrinkage into the proposed simple model seems promising and is necessary to provide an improved representation of the time-dependent behavior of prestressed concrete.